2012
DOI: 10.1186/1476-511x-11-37
|View full text |Cite
|
Sign up to set email alerts
|

Low fatness, reduced fat intake and adequate plasmatic concentrations of LDL-cholesterol are associated with high bone mineral density in women: a cross-sectional study with control group

Abstract: BackgroundSeveral parameters are associated with high bone mineral density (BMD), such as overweight, black background, intense physical activity (PA), greater calcium intake and some medications. The objectives are to evaluate the prevalence and the main aspects associated with high BMD in healthy women.MethodsAfter reviewing the database of approximately 21,500 BMD scans performed in the metropolitan area of São Paulo, Brazil, from June 2005 to October 2010, high BMD (over 1400 g/cm2 at lumbar spine and/or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Sarkis et al . found that subjects with a greater BMD presented a more favorable LDL profile, although there were no significant differences between them and women with a BMD considered normal for their age (femoral neck t‐score, 0.9 vs −0.2, P < 0.001; LDL cholesterol, 114 vs 124 mg/dL, P = 0.18) . Tarakida et al .…”
Section: Discussionmentioning
confidence: 94%
“…Sarkis et al . found that subjects with a greater BMD presented a more favorable LDL profile, although there were no significant differences between them and women with a BMD considered normal for their age (femoral neck t‐score, 0.9 vs −0.2, P < 0.001; LDL cholesterol, 114 vs 124 mg/dL, P = 0.18) . Tarakida et al .…”
Section: Discussionmentioning
confidence: 94%
“…Animal models support the association between osteoporosis and atherosclerosis (Parhami et al, 2000 ; Price et al, 2001 ). Observational studies have shown that higher atherogenic lipid profile and lipoproteins are inversely associated with bone density (Dimic et al, 2012 ; Sarkis et al, 2012 ) but the exact mechanisms underlying this relationship are unclear (Farhat and Cauley, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…MGP is a well-recognized potent inhibitor of arterial calcifications [38] and LDL-cholesterol is still considered one of the major determinants of atherosclerosis. Furthermore, some studies showed an association between LDL-cholesterol with BMD [39] and VFs [40] were associated with lower progression of aortic calcifications and increased survival in elderly men [41]. Taken together, these data strengthen the concept that bone fragility and vascular calcification may share some common pathways and that the presence of one of these two should prompt the clinicians to look for the other.…”
Section: Discussionmentioning
confidence: 64%